PROVIDING INCLUSIVE EDUCATION FOR DEAF STUDENTS IN THE POST-PANDEMIC UNIVERSITY CONTEXT - Ioana TUFAR (Universitaria Publishing House, Craiova, 2024)
Inclusive measures to ensure university education for Deaf students can be analyzed in the context of the bio-psycho-social model of disability in which we respect the particularities and value the real potential of the student. The approach that I propose for this paper is the bicultural- bilingual-bimodal way of regarding instruction, education and inclusion of Deaf Students. Taking into consideration just some theoretical aspects, I will focus more on pragmatical particularities that can interfere in the educational process of the Deaf Students from the point of view of the Sign Language Interpreter.